DAMPAK STRUKTUR PASAR DAN EFSIENSI TERHADAP KINERJA BANK PEMBANGUNAN DAERAH - Rizky Yudaruddin (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
Conditions Regional Development Bank (BPD) in terms of Business Growth, Markets and Competitiveness within the last three years shows an alarming condition. The study aims to assess the impact of market structure and efficiency of the performance of the BPD in Indonesia. The data used is secondary data in the form of financial statements of banks BPD in 2004-2013. The analytical tool used in this research is panel data regression. The results found that the banking industry in particular BPD in Indonesia supports the traditional hypothesis that assumes that the concentration is a proxy of market power (market power). Variable efficiency is not significant positive effect on the performance.Keywords: market structure, efficiency, performance, regional development banks